Developing Website for Belimbing Tourism Village, Tabanan, Bali - Ni Wayan Sintya Dewi; I Ketut Sutama; Ni Gst Nym Suci Murni; Made Sudiarta (International Journal of Glocal Tourism, 2023)
Purpose: The purpose of this research is to evaluate the Belimbing Village website in development efforts website by model information, communication, transaction, relationship and techical-merit (ICTRT) carried out to support the Belimbing Tourism Village produces dimensions of effectiveness website the maximum in helping the promotion of Belimbing Tabanan Tourism Village. Research methods: The data collection methods used were observation, interviews, questionnaires and interviews. In this study using qualitative and quantitative approaches or better known as mixed method research by using SWOT analysis techniques and Importance Performance Analysis. Findings: The results of the research using the interview method show that the application website in Belimbing Village is still very minimal because there are many features and items that need to be developed, one of which is the information dimension, transaction dimension and communication dimension. The results of the study using SWOT analysis showed that Belimbing Village has utilized ICT, but even though it has implemented ICT there are still many aspects that are lacking in website, so that more in-depth research is needed to assess its effectiveness in website Belimbing Village. Based on analysis Importance Performance Analysis produce effectiveness attributes. The researcher adopted the ICTRT model which consisted of 47 evaluation instruments which were divided into 5 evaluation dimensions. Implication: Site evaluation website expected to maximize promotion through website in Belimbing Village because website is an effective solution to introduce and market products/services by utilizing the internet as an information medium.